PENGARUH PROMOSI KESEHATAN TERHADAP PENGETAHUAN KADER DALAM MENGENDALIKAN HIPERTENSI PADA MASYARAKAT DI KELURAHAN BOJONG PONDOK TERONG KOTA DEPOK TAHUN 2021 - Annisa Dwi Kusumawati, (2021)
Based on data World Health Organization (2021), as many as 71% of the causes of death in the world are due to non-communicable diseases (NCDs). The most common NCDs suffered by the community in Bojong Pondok Terong Village is hypertension. Cadres can participate in disseminating knowledge to control hypertension in their area, but not all cadres have good knowledge about hypertension control. This study aims to determine the effect of health promotion on hypertension control through video on the knowledge of cadres in Bojong Pondok Terong Village. The design of this research is quantitative using pre-experimental approach through one group pre-post test design. The sample consisted of 79 health cadres. The data was taken in June 2021. The average result of the knowledge value of cadres during the pre-test was 11,43, then increased to 15,06 during the post-test. Then, the results of the Wilcoxon test showed a p-value of 0,000 (p < 0,05), it was concluded that there was an effect of health promotion on the knowledge of cadres in controlling hypertension. It is hoped that the cadres can provide education to families with hypertension sufferers so that the family also plays a role in monitoring their health status.